2012
DOI: 10.1016/j.nbd.2011.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and glia abnormalities in Tsc1-deficient forebrain and partial rescue by rapamycin

Abstract: Tuberous Sclerosis Complex (TSC) is a multiorgan genetic disease that prominently features brain malformations (tubers) with many patients suffering from epilepsy and autism. These malformations typically exhibit neuronal as well as glial cell abnormalities and likely underlie much of the neurological morbidity seen in TSC. Tuber pathogenesis remains poorly understood though upregulation of the mTORC1 signaling pathway in TSC has been consistently demonstrated. Here we address abnormal brain development in TSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
155
3
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(183 citation statements)
references
References 48 publications
19
155
3
1
Order By: Relevance
“…We previously found that suppression of Rheb-GTPase activity with farnesyl transferase inhibitors almost completely rescued spine synapse formation 14 . Thus, a non-canonical pathway such as this Rheb-syntenin signalling may participate in some of the symptomatic manifestations in TSC [40][41][42] . Indeed, knockdown and knockout of brain syntenin restored contextual fear discrimination deficits in Tsc2 þ / À rats and mice, respectively (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that suppression of Rheb-GTPase activity with farnesyl transferase inhibitors almost completely rescued spine synapse formation 14 . Thus, a non-canonical pathway such as this Rheb-syntenin signalling may participate in some of the symptomatic manifestations in TSC [40][41][42] . Indeed, knockdown and knockout of brain syntenin restored contextual fear discrimination deficits in Tsc2 þ / À rats and mice, respectively (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Emx1 Cre conditional knockout mice contain enlarged dysmorphic astrocytes within the cerebral cortex (Carson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Transgenic overexpression of mTOR in murine brains culminates in cortical atrophy and neurodegeneration (Kassai, Sugaya, Noda, Nakao, & Maeda, 2014), while conditional knockout of Tsc1 (TSC complex subunit 1), an mTOR inhibitor, has also successfully induced the neurodegenerative abnormalities in mouse brains, a phenocopy of AD pathophysiology (Carson, Nielen, Winzenburger, & Ess, 2012) (Table 2). At present, activation of mTOR has been recognized as a major event that causes AD pathogenesis (Yates, Zafar, Hubbard, Nagy, & Durant, 2013).…”
Section: The Important Role Of Protein Synthesis Pathways In Cancer Amentioning
confidence: 99%